Pengelolaan Pembelajaran Fisika Berbasis Masalah di SMA Negeri 2 Sukoharjo - Ikhwan, Ikhwan; , Prof. Dr. Bambang Sumardjoko, M.Pd; , Dr. Sofyan Anif, M.Si (2016)
This study aims general physics based learning management problems at school SMA Negeri 2 Sukoharjo. Particular goals, which describe about (1) Management of space and learning media Physics-based issues in order to improve student learning outcomes (2) The development of teaching material based physics problem (3) The interaction pembelajan physics-based problem (4) Planning evaluation and follow up Physics-based learning problems. This study used a qualitative research with phenomenological approach. Data collection techniques through in-depth interviews, observation, and documentation. Engineering analysis of data using multiple stages of data collection, data reduction, data presentation, and verification of data. Research results and solutions; (1) Risk Management space management and instructional media physics-based problem according to the learning needs of students so pembelajran can memeperkaya meaning good for teachers, students and the school in general (2) The development of teaching material based physics problems that need to be noticed is the procedure of development of teaching materials , identifying the early behavior of students, making the formulation of learning objectives, preparation and planning (3) Implementation of the learning interaction physics-based problem, students are required to work together in solving the problem (4) Planning evaluation and action learning physics-based problem, teachers engage students actively, so that students can understand the information provided by the teacher, students can find new information relationship with the information that has been studied, so that in the end the students can understand the information given by teachers to understand and learn the next teaching materials. Keywords: Management, Physics, Problem-based learning